(untitled) (American Journal of Islam and Society, 2013)
Jon Armajani’s book seeks to explain developments within Islam that have led to the rise of such radical Islamist groups as al-Qaida and the Taliban. The text provides an intellectual background for these movements in an attempt to explain how groups that profess to pursue religious objectives could justify engaging in horrific acts of terror. Armajani opens with a thirty-six-page introduction (including notes) in which he lays out the book’s theoretical foundations. He begins by defining Islamism as a subset of Islamic fundamentalism. His interest in al-Qaida and 9/11 quickly becomes clear, particularly in his discussion on whether or not the September 11 attacks could legitimately be viewed as acts of self-defense ...